The impact of South Africa's largest photovoltaic solar energy facility on birds in the Northern Cape, South Africa - Visser, Elke (Percy FitzPatrick Institute of African Ornithology, 2016)
Renewable energy is a promising alternative to alleviating fossil fuel-based dependencies, but its development can require a complex set of environmental trade-offs for bird communities in the area, ranging from effective and physical habitat loss to direct collision-related mortality. The wide variation in the nature and significance of predicted impacts of utility-scale photovoltaic (PV) facilities on birds, and the low levels of confidence attending these predictions, has emphasised the need for scientific research. This study assesses the risks to bird populations and guilds at one of South Africa's largest PV developments. Firstly, in order to identify functional and structural changes in bird communities in and around the development footprint, bird transect data were gathered, representing the solar development, boundary, and untransformed landscape. Secondly, to assess the risk of collision mortality with solar-related infrastructure, representative samples (core vs. edge) were surveyed for bird carcasses and other signs of collision for three months covering 20-30% of the facility at search intervals of 4, 7 and 14 days. In order to account for potential biases in carcass detection, searcher efficiency and carcass persistence trials were conducted. The distribution of birds in the landscape changed, from a shrubland to open country and grassland bird community, in response to changes in the distribution and abundance of habitat resources such as food, water and nesting sites. These changes in resource availability patterns were detrimental to some bird species and beneficial to others. Shrubland specialists, such as the black-chested prinia (Prinia flavicans) and chestnut-vented tit-babbler (Parisoma subcaeruleum), appeared to be negatively affected by the presence of the PV facility. In contrast, open country/grassland and generalist species, especially species such as the Cape sparrow (Passer melanurus) and familiar chat (Cercomela familiaris), were favoured by its development. Utility-scale PV facilities inevitably will not substitute for the natural habitats they have replaced, but might offer opportunities for climate protection that do not necessarily conflict with nature conservation. Monitoring success of avian mortality was significantly influenced by variation in detection rates by size class (60 and 95% for birds <100 g and >100 g, respectively) and the location of carcasses relative to the solar panel units (65 and 90% for birds adjacent and under the units, respectively) as well as decreasing persistence rates per search interval (57, 53, and 40% after 4, 7, and 14 days, respectively). Only injuries associated with non-fatal collision of large-bodied birds with the underside of the panels and entrapment between fencing could be concluded with reasonable certainty. An extrapolated fatality estimate of 4.53 fatalities.MW⁻¹.yr⁻¹ (95% CI 1.51-8.50), short study period, and lack of comparable results from other sources made it difficult to provide a meaningful assessment on avian mortality at PV facilities. Despite these limitations, the few bird fatalities that were recorded might suggest that there is no significant link with collision-related mortality at the study site. In order to fully understand the risk of solar energy development on birds, further collation and analysis of data from solar energy facilities across spatial and temporal scales, based on scientifically rigorous research designs, is required.